Key Performance Indicators For Business Financial Perspective (Journal of Namibian Studies : History Politics Culture, 2023)
Financials Key Performance Indicators (KPI) are crucial in strategic management for assessing and monitoring the main factors that determine the success of an organisation. This article aims to provide a list of generic key performance indicators for the financial perspective, classified by type, which can be used by managers to assess the current and future situation in different industries. The Systematic Literature Review (SLR) process involves defining research questions, setting inclusion and exclusion criteria, determining control group studies, creating a search string, obtaining candidate studies, refining selected studies, and analyzing them in full text. The result of the SLR includes six control group studies, 171 candidate studies, 119 selected studies, 109 retrieved papers, and 43 primary studies. These primary studies enable the identification of nine liquidity indicators, 29 activity indicators, 24 profitability indicators, and two debt indicators.